Susceptibility of neisseria gonorrhoeae strains to the antibiotics used for theatment of urethraland cervicaldischargeat a STD ambulatory in Manaus - Brazil - Ferreira, William A.; Sardinha, José Carlos G.; Schettini, Antonio P. M.; Ferreira, Cristina M.; Benzaken, Adele S. (Brazilian Journal of Sexually Transmitted Diseases, 2001)
Uackground: Gonorrhca is still an imponant discasc ali ovcr thc world with an incidence of 62 million cases. Ahhough this number is decli ning in devcloped countries, the d isease is still a serious public health problem in the devcloping countries. mainly dueto clinicai complications anel the capacity to intcnsify the transmission of HIV, The appearance of strains of N. go11orrrlweae resistant to antibiotics has been reporteei in severa! countries and this has become an additional concern for lhe organs of epidemie surveillance. Objectivc: ln the present study, wc used d isk diffusion test to evaluate the susceptibi lity of isolates of N. go11orrl,oeae to the antibiotics employed for the treatment of urethral anel cervical d ischarge ata DST clinic in Manaus. Results: Of thc 249 samplcs invcstigatcd samplcs, 175 (70,2%) wcrc rcsistant to tctracycline, 56 (22,4%) to penicillin anel 1 (0.4%) to erythromycin. Reduced sensibility was detected in 29 (11,6%) isolates tested against cefoxitin anel 12 (4,8) to erithromycin. Scnsibil ity of 100% of thc isolatcs was observed forceftriaxon, cefotaxin, cipro!loxacin anel ceftazid in. Conclusion: The high leveis of resistance detectcd, spccially for tetracycline anel pcnicillin, e mphasize the recommendations for not using these d rugs for the treatment of gonorrhea complicated. or not. Rcduced sensibility to cefoxitin and erythromycin, calls for caution in thc use of sccond gcncration ccfalosporins anel macrolides for treatment of that disease. Currcnt anel future control mcasurcs will also dcpcndon a pcrmanent anel effectivc clinicai anel laboratory monitoring of N. go11orrJ,oeae resistence to antibiotics